Cupreines and cupreidines: an established class of bifunctional cinchona organocatalysts - Bryant, Laura A.; Fanelli, Rossana; Cobb, Alexander J. A. (Beilstein Journal of Organic Chemistry, 2016)
Cinchona alkaloids with a free 6'-OH functionality are being increasingly used within asymmetric organocatalysis. This fascinating class of bifunctional catalyst offers a genuine alternative to the more commonly used thiourea systems and because of the different spacing between the functional groups, can control enantioselectivity where other organocatalysts have failed. In the main, this review covers the highlights from the last five years and attempts to show the diversity of reactions that these systems can control. It is hoped that chemists developing asymmetric methodologies will see the value in adding these easily accessible, but underused organocatalysts to their screens.
Keywords: bifunctional; cupreidine; cinchona; cupreine; organocatalysis

(untitled) - Li, H.; Liu, X.; Wu, F.; Tang, L.; Deng, L. (Proc. Natl. Acad. Sci. U. S. A., 2010)

(untitled) - Marcelli, T.; Hiemstra, H. (Synthesis, 2010)

(untitled) - Okino, T.; Hoashi, Y.; Takemoto, Y. (J. Am. Chem. Soc., 2003)

(untitled) - Okino, T.; Hoashi, Y.; Furukawa, T.; Xu, X.; Takemoto, Y. (J. Am. Chem. Soc., 2005)

(untitled) - Vakulya, B.; Varga, S.; Csámpai, A.; Soós, T. (Org. Lett., 2005)

(untitled) - Li, B.-J.; Jiang, L.; Liu, M.; Chen, Y.-C.; Ding, L.-S.; Wu, Y. (Synlett, 2005)

(untitled) - McCooey, S. H.; Connon, S. J. (Angew. Chem., Int. Ed., 2005)

(untitled) - Ye, J.; Dixon, D. J.; Hynes, P. S. (Chem. Commun., 2005)

(untitled) - Nodes, W. J.; Nutt, D. R.; Chippindale, A. M.; Cobb, A. J. A. (J. Am. Chem. Soc., 2009)

(untitled) - Rajkumar, S.; Shankland, K.; Brown, G. D.; Cobb, A. J. A. (Chem. Sci., 2012)

(untitled) - Rajkumar, S.; Shankland, K.; Goodman, J. M.; Cobb, A. J. A. (Org. Lett., 2013)

(untitled) - Al-Ani, W.; Shankland, K.; Cobb, A. J. A. (Synlett, 2016)

(untitled) - Marcelli, T.; van Maarseveen, J. H.; Hiemstra, H. (Angew. Chem., Int. Ed., 2006)

Comprehensive Enantioselective Organocatalysis: Catalysts, Reactions, and Applications - Ingemann, S.; Hiemstra, H. (Cinchonas and Cupreidines, 2013)

(untitled) - Morita, K.-i.; Suzuki, Z.; Hirose, H. (Bull. Chem. Soc. Jpn., 1968)

Japan Patent - Morita, K. (1968)

German Patent - Baylis, A. B.; Hillman, M. E. D. (1972)

(untitled) - Aggarwal, V. K.; Fulford, S. Y.; Lloyd-Jones, G. C. (Angew. Chem., Int. Ed., 2005)

(untitled) - Iwabuchi, Y.; Nakatani, M.; Yokoyama, N.; Hatakeyama, S. (J. Am. Chem. Soc., 1999)

(untitled) - Gaunt, M. J.; Johansson, C. C. C. (Chem. Rev., 2007)

(untitled) - Shi, M.; Xu, Y.-M. (Angew. Chem., Int. Ed., 2002)

(untitled) - Hu, F.-L.; Wei, Y.; Shi, M.; Pindi, S.; Li, G. (Org. Biomol. Chem., 2013)

(untitled) - Nakamoto, Y.; Urabe, F.; Takahashi, K.; Ishihara, J.; Hatakeyama, S. (Chem. – Eur. J., 2013)

(untitled) - Yoshida, Y.; Sako, M.; Kishi, K.; Sasai, H.; Hatekeyama, S.; Takizawa, S. (Org. Biomol. Chem., 2015)

(untitled) - Yao, Y.; Li, J.-J.; Zhou, Q.-Q.; Dong, L.; Chen, Y.-C. (Chem. – Eur. J., 2013)

(untitled) - Mohammadi, S.; Heiran, R.; Herrera, R. P.; Marqués-López, E. (ChemCatChem, 2013)

(untitled) - Hong, L.; Wang, R. (Adv. Synth. Catal., 2013)

(untitled) - Dalpozzo, R.; Bartoli, G.; Bencivenni, G. (Chem. Soc. Rev., 2012)

(untitled) - Chen, G.-Y.; Zhong, F.; Lu, Y. (Org. Lett., 2012)

(untitled) - Jayakumar, S.; Muthusamy, S.; Prakash, M.; Kesavan, V. (Eur. J. Org. Chem., 2014)

(untitled) - Huang, Y.-W.; Frontier, A. J. (Tetrahedron Lett., 2015)

(untitled) - Li, H.; Wang, B.; Deng, L. (J. Am. Chem. Soc., 2006)

(untitled) - Cochi, A.; Métro, T.-X.; Pardo, D. G.; Cossy, J. (Org. Lett., 2010)

(untitled) - Bandini, M.; Sinisi, R.; Umani-Ronchi, A. (Chem. Commun., 2008)

(untitled) - Corbett, M. T.; Johnson, J. S. (Angew. Chem., Int. Ed., 2014)

(untitled) - Montesinos-Magraner, M.; Cantón, R.; Vila, C.; Blay, G.; Fernández, I.; Muñoz, M. C.; Pedro, J. R. (RSC Adv., 2015)

(untitled) - Chauhan, P.; Chimni, S. S. (Tetrahedron Lett., 2013)

(untitled) - Li, H.; Wang, Y.; Tang, L.; Deng, L. (J. Am. Chem. Soc., 2004)

(untitled) - Wang, Y.; Liu, X.; Deng, L. (J. Am. Chem. Soc., 2006)

(untitled) - Wu, F.; Hong, R.; Khan, J.; Liu, X.; Deng, L. (Angew. Chem., Int. Ed., 2006)

(untitled) - Provencher, B. A.; Bartelson, K. J.; Liu, Y.; Foxman, B. M.; Deng, L. (Angew. Chem., Int. Ed., 2011)

(untitled) - Li, H.; Wang, Y.; Tang, L.; Wu, F.; Liu, X.; Guo, C.; Foxman, B. M.; Deng, L. (Angew. Chem., Int. Ed., 2004)

(untitled) - Li, Y.-Z.; Li, F.; Tian, P.; Lin, G.-Q. (Eur. J. Org. Chem., 2013)

(untitled) - Chauhan, P.; Chimni, S. S. (Adv. Synth. Catal., 2011)

(untitled) - Deng, Y.-Q.; Zhang, Z.-W.; Feng, Y.-H.; Chan, A. S. C.; Lu, G. (Tetrahedron: Asymmetry, 2012)

(untitled) - Das, U.; Chen, Y.-R.; Tsai, Y.-L.; Lin, W. (Chem. – Eur. J., 2013)

(untitled) - Tian, X.; Cassani, C.; Liu, Y.; Moran, A.; Urakawa, A.; Galzerano, P.; Arceo, E.; Melchiorre, P. (J. Am. Chem. Soc., 2011)

(untitled) - Bencivenni, G.; Galzerano, P.; Mazzanti, A.; Bartoli, G.; Melchiorre, P. (Proc. Natl. Acad. Sci. U. S. A., 2010)

(untitled) - Cabanillas, A.; Davies, C. D.; Male, L.; Simpkins, N. S. (Chem. Sci., 2015)

(untitled) - Aitken, L. S.; Hammond, L. E.; Sundaram, R.; Shankland, K.; Brown, G. D.; Cobb, A. J. A. (Chem. Commun., 2015)

(untitled) - Davis, R. L.; Stiller, J.; Naicker, T.; Jiang, H.; Jørgensen, K. A. (Angew. Chem., Int. Ed., 2014)

(untitled) - Zhu, Y.; Wang, Q.; Cornwall, R. G.; Shi, Y. (Chem. Soc. Rev., 2014)

(untitled) - Berkessel, A.; Guixà, M.; Schmidt, F.; Neudörfl, J. M.; Lex, J. (Chem. – Eur. J., 2007)

(untitled) - Arai, S.; Oku, M.; Miura, M.; Shioiri, T. (Synlett, 1998)

(untitled) - Lykke, L.; Rodríguez-Escrich, C.; Jørgensen, K. A. (J. Am. Chem. Soc., 2011)

(untitled) - Ji, C.-B.; Liu, Y.-L.; Zhao, X.-L.; Guo, Y.-L.; Wang, H.-Y.; Zhou, J. (Org. Biomol. Chem., 2012)

(untitled) - Zhou, F.; Zeng, X. P.; Wang, C.; Zhao, X.-L.; Zhou, J. (Chem. Commun., 2013)

(untitled) - Wang, Y.; Xiong, T.; Zhao, J.; Meng, Q. (Synlett, 2014)

(untitled) - Xiao, X.; Xie, Y.; Su, C.; Liu, M.; Shi, Y. (J. Am. Chem. Soc., 2011)

(untitled) - Wang, F.; Yang, C.; Xue, X.-S.; Li, X.; Cheng, J.-P. (Chem. – Eur. J., 2015)

(untitled) - Pei, C.-K.; Jiang, Y.; Shi, M. (Org. Biomol. Chem., 2012)

(untitled) - Wang, F.; Li, Z.; Wang, J.; Li, X.; Cheng, J.-P. (J. Org. Chem., 2015)

(untitled) - Li, C.; Jiang, K.; Chen, Y.-C. (Molecules, 2015)

(untitled) - Gao, T.-P.; Lin, J.-B.; Hu, X.-Q.; Xu, P.-F. (Chem. Commun., 2014)

(untitled) - Peng, J.; Ran, G.-Y.; Du, W.; Chen, Y.-C. (Org. Lett., 2015)

(untitled) - Yang, H.-B.; Yuan, Y.-C.; Wei, Y.; Shi, M. (Chem. Commun., 2015)

(untitled) - Jaiswal, P. K.; Biswas, S.; Singh, S.; Pathak, B.; Mobin, S. M.; Samanta, S. (RSC Adv., 2013)

(untitled) - Singh, S.; Srivastave, A.; Samanta, S. (Tetrahedron Lett., 2012)

(untitled) - Bogle, K. M.; Hirst, D. J.; Dixon, D. J. (Org. Lett., 2007)

(untitled) - Bogle, K. M.; Hirst, D. J.; Dixon, D. J. (Tetrahedron, 2010)

(untitled) - Bogle, K. M.; Hirst, D. J.; Dixon, D. J. (Org. Lett., 2010)